Transparência e interesse público: o trabalho de acesso à informação e comunicação pública na Câmara Municipal de Uberlândia - MG - Medeiros, Letícia Daniela Gonçalves (2021)
This research is based on public interests and transparency having as study object Uberlândia‘s city council. The study was created after social media and institutional website monitoring seeking to understand how legislative guidelines are presented to the population and also how e-Sic works in meeting the demands for information requests. Given these results one can observe how they works the issue of public communication and if the Access to Information Law norms have been respected. The methodology used was content analysis by watching Facebook and Instagram‘s posts in the light of Public Communication, Access to Information Law and Press Office and which data was collected between April and June 2020. Social media monitoring tools were used, respecting each of their specificities, to complement the analysis together with the language used in the communications. The official Chamber publications, O Legislativo journal, were analyzed to contextualize the analysis scenario as a way to understand the parliamentarian‘s discussions. Results show that public interests and transparency aren‘t effectively worked by the institution on social media and access to information in the website is deeply committed.